2012
DOI: 10.1371/journal.pone.0048961
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Biases toward Internet Game-Related Pictures and Executive Deficits in Individuals with an Internet Game Addiction

Abstract: BackgroundThe cue-related go/no-go switching task provides an experimental approach to study individual’s flexibility in changing situations. Because Internet addiction disorder (IAD) belongs to the compulsive-impulsive spectrum of disorders, it should present cognitive bias and executive functioning deficit characteristics of some of these types of disorders. Until now, no studies have been reported on cognitive bias and executive function involving mental flexibility and response inhibition in IAD.Methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 19 publications
4
66
0
4
Order By: Relevance
“…Moreover, when gamers found themselves paying attention to real life objects relevant to the videogame, it resulted in 'selective attention'. This is similar to individuals with gaming or alcohol problems that respond more to stimuli related to gaming or alcohol (Cox, Hogan, Kristian, & Race, 2002;Zhou, Yuan, & Yao, 2012).…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, when gamers found themselves paying attention to real life objects relevant to the videogame, it resulted in 'selective attention'. This is similar to individuals with gaming or alcohol problems that respond more to stimuli related to gaming or alcohol (Cox, Hogan, Kristian, & Race, 2002;Zhou, Yuan, & Yao, 2012).…”
Section: Discussionmentioning
confidence: 59%
“…measured event-related brain potentials during a color-word Stroop task and noted that Internetaddicted individuals showed longer reaction time and more response errors on the Stroop task and reduced medial frontal negativity, indicating impaired executive control ability. Zhou, Yuan, and Yao (2012) found that among individuals with Internet game addiction, cognitive bias and executive function constructs involving mental flexibility and response inhibition were worse among longer-term users. Park et al (2011) also found impaired performance related to attention among individuals who had IAD for a longer period of time.…”
Section: Cognitive Factors Associated With Problematic Internet Usementioning
confidence: 98%
“…Further, Internet gaming addiction (IGA) presents cognitive biases toward information related to Internet gaming. These biases, as well as poor executive functioning skills (lower mental flexibility and response inhibition), might contribute to IGD [41]. Although these studies reported that cognitive characteristics associated with substance use disorder are similar to those in IGD, the number of reports is limited.…”
Section: Neurocognitive Studies Of Igdmentioning
confidence: 99%